THE MODEL OF DETECTING LEGISLATION VIOLATORS AT THE STATE BORDER USING FUZZY LOGIC INFERENCE - Oleksandr S. Androshchuk; Oleksandr V. Mikhaylenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The analysis showed the existing information and telecommunications systems are not able to make enough timely and quality support decision-making on criminal analysis and require further improvement.